Synthesis of Al-Containing Spherical Mesocellular Silica Foams with Different Pore Sizes and Their Applications as Catalyst Supports for Hydrodesulfurization of Dibenzothiophene - Zhou, X.; Song, S.; Duan, A.; Zhao, Z.; Gong, Y.; Wang, X.; Li, J.; Wei, Y.; Jiang, G.; Liu, Jian (WILEY-V C H VERLAG GMBH, 2015)
© 2015 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim. In the present work, a series of Al-containing spherical mesostructured cellular silica foams (SMCFs) with different ultra-large pore sizes were successfully synthesized by simply adjusting the mass ratio (x) of the swelling agent 1,3,5-trimethylbenzene (TMB) to P123. The as-synthesized Al-SMCFs-x were utilized as NiMo catalyst supports for the hydrodesulfurization of dibenzothiophene. The characterization results showed that, compared with other studied NiMo/Al-SMCFs-x catalysts, the NiMo/Al-SMCFs-1.25 catalyst exhibited higher sulfidation degree, higher dispersions of Ni and Mo species, shorter length, and lower stacking number of MoS 2 slabs. It was also found that the NiMo/Al-SMCFs-1.25 catalyst possessed suitable physicochemical parameters [i.e., ultra-large pore size (27.5 nm), high surface area (383 m 2 g -1 ), and large pore volume (1.34 cm 3 g -1 ), resulting in the formation of more type II active sites with more brim active sites. Consequently, the NiMo/Al-SMCFs-1.25 catalyst displayed outstanding catalytic performance for the hydrodesulfurization of dibenzothiophene. Superb supports: A series of NiMo/Al-SMCFs-x (SMCFs=spherical mesostructured cellular silica foams) catalysts with different ultra-large mesopore sizes are successfully synthesized by simply adjusting the 1,3,5-trimethylbenzene/P123 mass ratio (x). Among all the studied catalysts, NiMo/Al-SMCFs-1.25 exhibited the best dibenzothiophene (DBT) hydrodesulfurization (HDS) performance. DDS=direct desulfurization, HYD=hydrogenation, CHB=cyclohexylbenzene, BP=biphenyl.